Monetary Policy and Demographics: Empirical Evidence for Housing Prices in Indonesia - Alghifari Mahdi Igamo; Azwardi Azwardi; Ardi Saputra; Rizky Ghoffar Ismail; Gustriani Gustriani; Vinny Dwi Melliny (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
The housing market in Indonesia has different characteristics for each region. These differences underlie changes in house prices, factors that affect house prices include Loan to Value (LTV), mortgage rate, income, and population. The data was obtained from relevant agencies of Bank Indonesia and the Statistics Indonesia, using data from 2012-2021, which is a combination of time-series data and a cross-section of 18 cities in Indonesia. The research method used is a regression panel. The results of the study of income levels, population, and Loan to Ratio (LTV) are significant to house prices, except for mortgage rates which not be effective in depressing housing price during the observation period.